Design and construction of houses with Guadua cane and rice husk in Ecuador as an alternative to local development - Pedro José Rodríguez Gómez; Adela María Gacía Yero; Guberto Cánovas Riverón (Sustainable Structures)
The use of sustainable construction materials as a response to habitat problems is one of the urgent alternatives for Ecuador. The country has a high production of rice, an intensive crop that generates a high volume of polluting waste that is not efficiently managed, which causes damage to the environment. The purpose of the research was to design a sustainable construction system with the joint use of Guadua cane, of ancestral domain, and rice husk as components of a hybrid lightweight concrete. As a result, two houses were built in 1992 and 2020, respectively, validating the feasibility of the proposal. A flexible, resistant, sustainable system is achieved, which takes advantage of local resources, both traditional and alternative, that allow to give an answer to the habitat with a good aesthetic finish. It is an alternative for the local development of autonomous governments that allows the construction of decent, durable and comfortable housing, with the use of their own resources and in accordance with the country's traditions.